1995
DOI: 10.1038/ki.1995.474
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide receptors A and B have different cellular distributions in rat kidney

Abstract: The cellular distribution of guanylyl cyclase coupled natriuretic peptide receptors type A (GC-A) and type B (GC-B) was examined by immunocytochemistry in normal rat kidney, and compared with the distribution of the vacuolar H(+)-ATPase. Staining for GC-A was found in glomeruli, thin limbs of Henle's loop, cortical collecting tubule, and inner medullary collecting duct. Staining for GC-B was found in glomeruli and the same nephron sections as GC-A, with the exception of the thin limbs. In the cortical collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…CNP is inactivated by NEP, and therefore local CNP may be degraded before arrival in the lumen of the collecting duct, offering a plausible explanation for its weak natriuretic effect. 29 In summary, we demonstrated that CNP expression tends to be higher immediately after ligation and declined at later time points. A high level of CNP may contribute to the elevated expression of NPR-B in the early phase of UUO.…”
Section: Discussionmentioning
confidence: 93%
“…CNP is inactivated by NEP, and therefore local CNP may be degraded before arrival in the lumen of the collecting duct, offering a plausible explanation for its weak natriuretic effect. 29 In summary, we demonstrated that CNP expression tends to be higher immediately after ligation and declined at later time points. A high level of CNP may contribute to the elevated expression of NPR-B in the early phase of UUO.…”
Section: Discussionmentioning
confidence: 93%
“…The latter hypothesis may explain why renal NPR-Bs are not detectable with autoradiography 50 or radioreceptor-binding assay. 53 In addition, Ritter et al 52 found that the cellular distribution of NPR-Bs is quite different from that of NPRAs. NPR-As were detected in glomeruli, thin limbs of Henle loop, cortical collecting ducts, and inner medullary collecting duct.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with the evidence that within the kidney, CNP stimulates less cGMP generation than does ANP, 49,50 even if NPR-Bs are expressed in the kidney. 49,51,52 This blunted response may be due to either an intrinsically low guanylate cyclase activity of NPR-B or a low number of these receptors. The latter hypothesis may explain why renal NPR-Bs are not detectable with autoradiography 50 or radioreceptor-binding assay.…”
Section: Discussionmentioning
confidence: 99%
“…17 GC-A is abundantly expressed in blood vessels and the heart 17 ; within the kidney, it is localized in glomeruli, thin limbs of Henle's loop, cortical collecting ducts, and inner medullary collecting ducts. 18 In glomeruli, GC-A is expressed in mesangial cells and podocytes. 18 GC-A-deficient mice show chronic salt-independent elevation of BP by approximately 15-30 mmHg 19 and cardiac hypertrophy, 20 with virtually no natriuretic or diuretic response to acute volume expansion.…”
mentioning
confidence: 99%
“…18 In glomeruli, GC-A is expressed in mesangial cells and podocytes. 18 GC-A-deficient mice show chronic salt-independent elevation of BP by approximately 15-30 mmHg 19 and cardiac hypertrophy, 20 with virtually no natriuretic or diuretic response to acute volume expansion. 21 These studies clearly demonstrate essential roles for natriuretic peptide/GC-A signaling in BP regulation and acute volume handling through the kidney, but the role of GC-A in podocyte injury remains elusive.…”
mentioning
confidence: 99%